Pengaruh Bimbingan Kelompok Teknik Mind Mapping terhadap Peningkatan Kreativitas Belajar Siswa SMP - Mochamad Tazkiya Fuadi; Meilla Dwi Nurmala (ARZUSIN, 2026)
Although learning creativity has received attention in several previous studies, research that specifically examines the effect of group guidance using the mind mapping technique on enhancing students’ learning creativity at the junior high school level remains limited. This study aimed to analyze the effect of group guidance with the mind mapping technique on improving students’ learning creativity. A quantitative approach with a pre-experimental one-group pretest–posttest design was employed, involving eighth-grade students of SMPN 6 Malingping in the 2025/2026 academic year selected through purposive sampling. Data were collected using a learning creativity scale and analyzed with the Wilcoxon Signed Rank Test. The results showed an increase in students’ learning creativity after the provision of group guidance services using the mind mapping technique, as indicated by a significant difference between pretest and posttest scores. These findings contribute to the development of learning creativity theory and broaden understanding of the effectiveness of innovative guidance and counseling services in school settings. The study concludes that the use of the mind mapping technique in group guidance is important for enhancing students’ learning creativity and recommends that guidance and counseling teachers integrate this technique into service delivery. The implications of this research include theoretical contributions to the literature on learning creativity and practical implications for schools in developing guidance services that are creative and responsive to students’ needs, while also opening opportunities for further exploration of the application of the mind mapping technique at different educational levels and with different variables.